Government accounting : a self-instructional approach - Pobre, Hermogenes P.; Bernal-Magno, Araceli (Philippines : [publisher not identified], 1987)
This book is an attempt to present an organized operational guide to government accounting as practiced in the National Government. It is a subject which, in the light of recent development as mandated by law, has been accorded renewed importance.
1. Accounting responsibility, nature and scope -- 2. Funds -- 3. The national budget -- 4. The standard chart of accounts and the generally accepted accounting principles on accounts -- 5. Income, receivables and collections -- 6. Appropriation, allotments and obligations -- 7. Cash disbursement ceiling and disbursements -- 8. Miscellaneous transactions -- 9. The trial balance and other financial statements -- 10. Bank and treasury reconciliation -- 11. The decentralized accounting procedures -- 12. Local government accounting system.
Keywords: ACCOUNTING